Physical versus virtual manipulative experimentation in physics learning - Zacharia, Zacharias C.; Olympiou, Georgios (My University, 2011)
The aim of this study was to investigate whether physical or virtual manipulative experimentation can differentiate physics learning. There were four experimental conditions, namely Physical Manipulative Experimentation (PME), Virtual Manipulative Experimentation (VME), and two sequential combinations of PME and VME, as well as a control condition (i.e., traditional instruction with absence of PME or VME). Undergraduate students' understanding of physics concepts in the domain of heat and temperature was tested in a pre- and posttest design that involved 182 participants assigned to the four experimental groups and 52 participants assigned to the control group. Conceptual tests were administered to assess students' understanding before, during and after instruction. The analyses revealed that the four experimental conditions were equally effective in promoting students' understanding of concepts in the domain of heat and temperature and better than the control condition; hence, manipulation, either physical or virtual manipulation, and not physicality, as such, at least in a context like the one of the present study, is important in physics learning.
Keywords: Touch; Physics; Experimentation; Laboratory; Simulations; Virtual labs